Analysis of Tensile Strength and Water Absorption Properties of Glass-Ramie Hybrid Laminated Composite - Yudhanto, Ferriawan (Universitas Muhammadiyah Yogyakarta, 2023)
Hybrid layered composites (HLC), combining natural and synthetic fibers, are mainly used in the automotive composite industry. The factor determining the inter-mechanical bond between layers impacts the mechanical strength.. Ramie fibers were immersed in a 5 wt.% NaOH solution for 2 hours to remove lignin and hemicellulose content in the fiber surface. Alkali treatment increases the adhesion bond between cellulose and the polyester matrix. The treated ramie fibers to be weaved by traditional machine to produce the woven ramie. The three-layer fibers are manufactured by press mold with a 2-bar pressure. The characterization of HLC for tensile strength according to ASTM D638 and water absorption refers to ASTM D570. The excellent tensile strength and elastic modulus of HLC have a stacking sequence of woven ramie-unidirectional glass-woven ramie (WR-UG-WR) by 150 MPa and 24.1 GPa, respectively, and its lowest water absorption by 3.31%.